Practicality Analysis of Career E-Module Development to Enhance Students' Career Planning at SMAN 1 Dampal Selatan - Mirdan, Moh (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2025)
This study aims to analyze the practicality of the Career E-Module developed as a learning medium to support students' career planning. The practicality test was conducted on October 10–11, 2024, involving one Guidance and Counseling (BK) teacher and ten students from two classes as respondents. The evaluation utilized a Likert scale questionnaire and Focus Group Discussion (FGD) to obtain qualitative and quantitative data. The results showed that the Career E-Module is highly practical, with an average score of 93% from the guidance and counseling teacher and 88.25% from the students, both categorized as "Highly Practical." The counseling and guidance teacher found that E-Module is easy to use, relevant, and very helpful for classical service. Qualitatively, students gave positive feedback regarding the design and content. They stated that the module is visually interesting and meets their needs. Through the FGD, students gave suggestion to add a variety of career options as references, enlarging font size for better readability, and improving consistency of content by using supporting videos. These critics and suggestions becomes basis for doing product revisions to enhance the quality and utility of the E-Module. The strength of this E-Module compared to traditional methods is in its flexibility, attractive design, and integration of interactive media such as YouTube videos, which enhance students' understanding. This study showed that the Career E-Module is effective and relevant in supporting both students and guidance and counseling teacher (BK) teachers in formulating the career planning. Although it is already rated as highly practical, revisions addressing feedback from teachers and students will further optimize its use.